2009
DOI: 10.4049/jimmunol.0803447
|View full text |Cite
|
Sign up to set email alerts
|

M1 and M2a Polarization of Human Monocyte-Derived Macrophages Inhibits HIV-1 Replication by Distinct Mechanisms

Abstract: The capacity of macrophages to support productive HIV-1 infection is known to be modulated by cytokines and other extracellular stimuli. In this study, we demonstrate that cytokine-induced polarization of human monocyte-derived macrophage (MDM) into either classical (M1) or alternatively activated (M2a) MDM is associated with a reduced capacity to support productive CCR5-dependent (R5) HIV-1 infection. M1 polarization was associated with a significant down-regulation of CD4 receptors, increased secretion of CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
206
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(237 citation statements)
references
References 79 publications
24
206
2
5
Order By: Relevance
“…HIV-1 replication was lower in M2a cells compared with M0 MDMs and was almost totally inhibited in M1 MDMs (Fig. 7B), which is in agreement with previous observations (72). Analysis of BAFF secretion in infected or uninfected polarized or control MDM supernatants following 12 d of incubation revealed that HIV-1 stimulates BAFF production in M0 and M2a MDMs but not in M1 cells (Fig.…”
Section: Hiv-1-mediated Baff Induction Is Modulated By the Macrophagesupporting
confidence: 80%
“…HIV-1 replication was lower in M2a cells compared with M0 MDMs and was almost totally inhibited in M1 MDMs (Fig. 7B), which is in agreement with previous observations (72). Analysis of BAFF secretion in infected or uninfected polarized or control MDM supernatants following 12 d of incubation revealed that HIV-1 stimulates BAFF production in M0 and M2a MDMs but not in M1 cells (Fig.…”
Section: Hiv-1-mediated Baff Induction Is Modulated By the Macrophagesupporting
confidence: 80%
“…After 5-6 days, these MDMs (Ͼ95% CD14) were stimulated by IFN␥ (50 ng/ml) and LPS (10 ng/ml) or IL4 (50 ng/ml) for another 24 h (supplemental Fig. 2) (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…After 5-6 days, these MDMs (Ͼ95% CD14) were stimulated by IFN␥ (50 ng/ml) and LPS (10 ng/ml) or IL4 (50 ng/ml) for another 24 h (supplemental Fig. 2) (25,26).Transfection and Transduction-siRNA and/or plasmids were transfected into the cells by using Lipofectamine Plus reagent according to the manufacturer's instructions (Invitrogen). Overexpression of Rev-erb␣ was performed by infecting primary human monocyte-derived macrophages with adenoviral particles (500 -1000 plaque-forming units/cell) in Opti-MEM for 2-4 h followed by the addition of fresh medium and additional incubation of 24 h.…”
mentioning
confidence: 99%
“…96 In addition, polarization is extremely important as it shifts macrophages from a state of active to latent viral infection. 97 A model was proposed in which macrophages changed from M1 to M2 polarization during the transition from early to late stage disease, which promoted their latent infection and the formation of a steady-state viral reservoir. 98 The loss of a polarized phenotype promoted active macrophage viral replication and the production of infectious virus, 97 suggesting that polarization-reversing agents must be considered when developing shock and kill therapeutic strategies.…”
Section: Cd68mentioning
confidence: 99%